1968
DOI: 10.9753/icce.v11.72
|View full text |Cite
|
Sign up to set email alerts
|

Solid and Permeable Submerged Breakwaters

Abstract: The behaviour of thin and rectangular solid submerged breakwaters is re-examined. Dean's theory is found to be correct for a thin barrier in infinitely deep water. An empirical and theoretical relationship for the reflection coefficient of a thin breakwater across the wave number spectrum is proposed. Rectangular solid breakwaters have a maximum reflection when the incident wave has the same period as a standing wave on top of the breakwater and with a wave length equal to the crest width. A submerged permeabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The physical experiments and theoretical results (e.g. Dick and Brebner, 1968;Hsu and Wu, 1998;Wang and Shen, 1999;Usha and Gayathri, 2005) showed that the optimum width of a simple, fixed plate was around 0.32-0.5 of the incident wavelength. Thus it is important to know when and where such a local minimum appears in a vegetated platform.…”
Section: Resultsmentioning
confidence: 99%
“…The physical experiments and theoretical results (e.g. Dick and Brebner, 1968;Hsu and Wu, 1998;Wang and Shen, 1999;Usha and Gayathri, 2005) showed that the optimum width of a simple, fixed plate was around 0.32-0.5 of the incident wavelength. Thus it is important to know when and where such a local minimum appears in a vegetated platform.…”
Section: Resultsmentioning
confidence: 99%
“…There have been extensive research on the wave blocking performance of an SHP and the mechanism behind the performance. Dick and Brebner [1968] probably conducted the earliest experiment to investigate the wave re°ection and transmission of the SHP as a limit case of a permeable submerged rectangular. The method of matched asymptotic expansions was applied by Siew and Hurley [1977] to derive analytical expressions for the re°ection and transmission coe±cients of long wave by the SHP.…”
Section: Introductionmentioning
confidence: 99%
“…Submerged structures to protect beaches have become popular recently because they are widely perceived as being capable of providing the necessary beach protection (Dean, Chen, and Browder, 1997) without any loss of beach amenity (Ranasinghe and Turner, 2006). Submerged breakwaters were used to protect harbor entrances, to control wave action at inshore fishing grounds, and to reduce the rate of littoral drift early in 1960s (Dick and Brebner, 1968). Many papers (Chang and Liou, 2007;Mendez, Losada, and Losada, 2001;Tunji, Hashim, and Yusof, 2012) have discussed the effects to waves caused by submerged breakwaters.…”
Section: Introductionmentioning
confidence: 99%